Discursos y «paltas» de los jóvenes universitarios sobre su sexualidad en un marco de relaciones igualitarias * - Fermi, Ennio (2006)
In the frame of the new egalitarian relationships that are being woven between men and women, this paper explores the fears that young men have about these changes. The central question refers to, what happens to young men when they are socialized in traditional schemes and must confront a social space where gender relationships reconfigure and allow new sexual practices, like casual relationships or relationships without commitment? Our answer is supported by a preliminary typology of fears that give this research means to understand this phenomenon which is part of the world of Lima’s young people. By means of analyzing the discourse of young male students of a private university, we can shed new light on the transition from a traditional model based on male domination to a recent liberated model that tends toward equality in gender relations.